Pengaruh Pemberian Simulasi Penanggulangan Bencana Tanah Longsor Terhadap Sikap Siswa di Sekolah Dasar Negeri 1 Selo Boyolali - Emi Septiana; Akbar Amin Abdullah; Rizal Fajri (Lembaga Pengembangan Kinerja Dosen, 2024)
Landslide disasters can cause death and have a major impact on health systems and important services such as water, electricity or communication lines. The positive attitude shown by students is the initial milestone in changing attitudes to support student preparedness behavior. Through a landslide disaster management simulation, students' attitudes become positive and are able to apply self-evacuation techniques when a landslide occurs in accordance with the SOP for landslide disaster management. To determine the effect of providing a landslide disaster management simulation on students' attitudes at Selo Boyolali 1 State Elementary School. Research method: This type of research is pre-experimental design without control group with a one group pretest posttest design. The sampling technique used was purposive sampling, a sample of 29 students. Measuring student attitudes uses a student attitude questionnaire sheet consisting of 20 statement items using a Likert scale. Before the research was carried out the average results were 51.21% and after the research the average results were 67.45%, in other words Posttest > Pretest. Then the Wilcoxon test was carried out and the result was that P-Value = 0.001 (P<0.05) Ha was accepted. There is an influence of providing a landslide disaster management simulation on the attitudes of students at the Selo Boyolali 1 State Elementary School